SEXUALLY TRANSMITTED INFECTION AWARENESS AND RISKY SEXUAL BEHAVIOURS: ARE SINGLE MALE MIGRANTS IN INDIA LEFT BEHIND? A CROSS-SECTIONAL STUDY - M Shashi Kumar; Seema P; Ameenah Anwar Hussain Siraja (Journal of Public Health Research and Community Health Development, 2026)
Background: Single Male Migrants (SMMs) are highly vulnerable and at high risk of acquiring and spreading sexually transmitted infections (STIs) due to a lack of social support networks, unstable legal status, cultural and language barriers, high mobility, stress from adapting to new environments, economic difficulties, and a lack of health insurance and education. Purpose: Our study uniquely addresses a largely overlooked population - Single Male Migrants (SMMs) in Bengaluru, India. This study is the first to assess STI awareness and risky sexual behaviors and also pinpoints the major challenges encountered by this group. These findings are instrumental in bolstering policies and services pertaining to migrant health in India. Methods: A cross-sectional study was conducted among 440 SMMs from the community and Integrated Counselling and Testing Centre (ICTC), in urban Bengaluru, to assess their STI awareness and risky behaviors. Informed consent was obtained, and data were collected using a structured, pre-tested questionnaire using Epi Collect version 5 and analysed using IBM SPSS 22.0. Results: Of the 440 SMMs, only 25% had good awareness of sexually transmitted infections (STIs). Around 31.8% of migrants had STI symptoms, but none received treatment. Risky sexual behaviors were noted among these single men with only few (6.3%) using condoms. Conclusion: The low STI awareness and risky behaviors among SMMs underscore the urgent need to enhance STI health education.